Implications of Look AHEAD for clinical trials and clinical practice. Issue 12 (22nd June 2014) - Wing, R. R.; for The Look AHEAD Research Group
<x xml:space="preserve">Abstract</x> Look AHEAD (Action for Health in Diabetes) was a randomized clinical trial designed to examine the long‐term health effects of weight loss in overweight and obese individuals with type 2 diabetes. The primary result was that the incidence of cardiovascular events over a median follow‐up of 9.6 years was not reduced in the Intensive Lifestyle Group relative to the control group. This finding is discussed, with emphasis on its implications for design of trials and clinical treatment of obese persons with type 2 diabetes.